Literature Review: Pengaruh Motivasi, Lingkungan Kerja, dan Insentif Terhadap Kinerja Karyawan: indonesia - Ikhsan Amar Jusman (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Human resources are an important element so that a company or business can run well. Without these elements or the quality of these elements is not good, it will have an impact on the development and progress of the company which is difficult to run as expected, increasing the effectiveness of employee performance, there are some employees do not work according to the standards set by the company. Therefore, motivation, work environment and incentives are expected to encourage and direct employees to work better to achieve company goals. This research uses qualitative methods. Qualitative research involves researchers to gain an understanding of the context and natural phenomena being studied. The aim of qualitative research is to gain an understanding of the conditions of the context through a detailed and in-depth explanation of the conditions in the natural environment so as to obtain results in a company. Human resources are a fairly important aspect in achieving the vision. and the company's mission, therefore it is important for companies to pay attention to safety in the work environment, providing motivation and incentives is also very important to improve employee performance. Judging from several previous studies, it is stated that Motivation, Work Environment and Incentives influence employee performance. By providing a proper work environment, providing motivation and incentives, employees will be able to do their work optimally because employees have the opportunity to improve their respective performance